RETRACTED - Performed Interventions, and Public Claims: A Study of Solid Waste Management by Khadak Municipality (Patan Pragya, 2019)
Retraction Notice: On 18th September 2023, the Editors of Patan Pragya decided to retract this article after the author identified three types of errors in the article: a) grammatical errors; b) research paper internal structuring errors; and c) referencing errors.